Intersystem EMC analysis, interference, and solutions - Vered, Uri (Artech House electromagnetic analysis series., 2018)
This comprehensive new resource provides methods and tools for defining EMC requirements and techniques for performing predictions and calculations to achieve electromagnetic compatibility. This book demonstrates how radar, communications, and navigation systems can function without interference. EMC requirements for the device, platform, site, and arena level are discussed and EMC detection analysis is utilized to predict EMC problems. The book explores the interference between receiving and transmitting electronic systems and examines intersystem and intrasystem EMC.nnTechniques and mathematical framework for performing EMC prediction and calculations to solve electromagnetic compatibility problems are highlighted. Moreover, this book presents classic methods and several original EMC calculation procedures including new approaches in mathematical development of interference probability calculations. Readers learn how to anticipate problems and then define EMC solutions.